Integrating the AMORA learning model and KOBIAS manipulative media for enhancing elementary students’ mathematical conceptual understanding: A quasi-experimental study - Nina Rostiana; Mubiar Agustin; Sandi Budi Iriawan (Journal of Advanced Sciences and Mathematics Education, 2026)
Background: Elementary students’ mathematical conceptual understanding remains a critical challenge because mathematics instruction often emphasizes procedural knowledge rather than meaningful concept construction. Although learner-centered pedagogies and manipulative media have individually demonstrated positive effects on mathematics learning, empirical evidence regarding their integrated implementation is still limited. Aims: This study investigated the effect of integrating the AMORA learning model with KOBIAS (Kotak Bilangan Asli) manipulative media on elementary students’ mathematical conceptual understanding. Method: A quasi-experimental study employing a nonequivalent control group design was conducted with fifth-grade students selected through cluster random sampling. The experimental group received instruction using the integrated AMORA–KOBIAS approach, whereas the control group experienced conventional instruction. Data were collected through a validated mathematical conceptual understanding test and analyzed using descriptive statistics, normality and homogeneity tests, an independent-samples t-test, and normalized gain (N-gain) analysis. Results: The experimental group significantly outperformed the control group (p < .05), achieving a higher mean post-test score (70.26 vs. 38.83). Moreover, the N-gain analysis indicated a moderate-to-high improvement in students’ mathematical conceptual understanding following the intervention. Conclusion: Integrating the AMORA learning model with KOBIAS manipulative media effectively enhances elementary students’ mathematical conceptual understanding by promoting active concept construction through learner-centered instruction and concrete mathematical representations. This approach offers an effective instructional alternative for strengthening conceptual learning in elementary mathematics.